Development and Characterization of Crackers Substitution of Wheat Flour With Jellyfish - Maisont, Suchada; Samutsri, Wisutthana; Phae-ngam, Wuttichai; Limsuwan, Pichet (Frontiers in Nutrition, 2021)
The objective of this study was to investigate the possibility of using jellyfish (Lobonema smithii) for production of nutritionally improved crackers. In this study, ground jellyfish was incorporated in different levels (0%, 20%, 30%, and 40%) to replace wheat flour in cracker formula. Physico-chemical characteristics and sensory quality of the developed crackers were examined and compared with control crackers. The crackers with jellyfish were found significantly darker, more fractability, and less consumer accepted than the control samples (p < 0.05). Moisture content, aw, and TBARS values of jellyfish crackers increased while hardness of the jellyfish crackers decreased with increasing the storage time for both crackers stored at 35 ºC and 45 ºC. The substitution of wheat flour with jellyfish led to high protein content in the crackers. The cracker with 30% of jellyfish gained characteristic of cracker, liking scores, as well as the subjective quality of the final product and had good physical and chemical conditions, being able to be consumed for a period of 12 weeks stored at 35 ºC.